The Influence of Personal Characteristics, Interaction: (Computer/Individual), Computer Self-efficacy, Personal Innovativeness in Information Technology to Computer Anxiety in use of Mind your Own Business Accounting Software - Mayasari, Mega; ., Gudono (International Journal of Economics and Financial Issues, 2015)
The purpose of this study was to identify the factors that cause computer anxiety in the use of Mind Your Own Business (MYOB) accounting software, i.e., to assess if there are any influence of age, gender, amount of training, ownership (usage of accounting software on a regular basis), computer self-efficacy, personal innovativeness in Information Technology (IT) to computer anxiety. The study also examined whether there is a relationship trait anxiety and negative affect to computer self-efficacy. The research data is obtained through questionnaires which was distributed to 100 vocational teachers at the accounting Department in the Riau Islands Province. However, only 82 questionnaires can be used. Data were analyzed using partial least square structural equation modeling. The results of this study indicate that there is a negative effect of the use of MYOB accounting software on a regular basis, computer self-efficacy, and personal innovativeness in IT to computer anxiety. Subsequent findings indicate that the trait anxiety has a negative effect on computer self-efficacy. However, these findings did not show any influence of age, gender, training and computer anxiety. Negative affect were also found not to have a relationship with computer self-efficacy. Keywords: Computer Anxiety; Self-efficacy; Innovativeness, Interaction: Computer/Individual; Accounting Software JEL Classifications: M00